Can you certify your software to MC/DC? A static analysis approach to account for the number test cases - Martins, Alexandre L.; Melo, Ana C. V. de (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2016: Anais do I Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2016)
Software testing is an important task in systems development to certify the quality of the final product. If it is not properly applied, we can end up with low-quality systems. On the other hand, applying rigorous software testing techniques can spend nearly 40-50% of the system development cost. The issue is: how to provide a good software quality, by means of testing techniques, and keep the overall system cost under control?This paper presents a study on the cost of applying the Modified Condition/Decision Coverage (MC/DC) (proposed by NASA1 and used by FAA2 [19]) to software by accounting for the number of test cases that need to be generated. In order to achieve our goal, we collected the MC/DC coverage requirements in a set of open source software to estimate the cost of this criterion application in terms of the number of test cases.